PENERAPAN E-LKPD BERBASIS PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR PADA MATERI STRUKTUR ATOM DI SMA NEGERI 2 TOMOHON - Br Sinuhaji, Ayu Lestarina; Tuerah, Jeane M.; Rampe, Meytij J. (SOSCIED, 2024)
The aim of this research is to increase knowledge in the application of E-LKPD in chemistry learning in an effort to improve student activities and learning outcomes in atomic structure material at SMA Negeri 2 Tomohon. This research is classroom action research, the sample in this research is class X IPA 1 in implementing E-LKPD based on the CTL (Contextual Teaching and Learning) approach to atomic structure material. Data is collected through activities, responses and student learning outcomes. The research results showed that the percentage of student activity for cycle I, cycle II and cycle III was 85%, 96% and 100% respectively, student learning response was 84%. Student learning outcomes in cycle I, cycle II and cycle III were 60%, 92% and 100%. Student activity, response and learning outcomes increase with the application of the Contextual Teaching and Learning model to atomic structure material which can improve student learning outcomes.